Gallic Acid Suppressed Tumorigenesis by an LncRNA MALAT1-Wnt/β-Catenin Axis in Hepatocellular Carcinoma - Shi, Chuan-jian; Zheng, Yan-biao; Pan, Fei-fei; Zhang, Feng-wei; Zhuang, Peng; Fu, Wei-ming (Frontiers in Pharmacology, 2021)
Gallic acid (3,4,5-trihydroxybenzoic acid; GA), a natural phenolic acid, is abundantly found in numerous natural products. Increasing studies have demonstrated that GA plays anti-cancer roles in multiple cancers. However, its anti-tumor effects on hepatocellular carcinoma (HCC) and the underlying mechanism remain obscure. In the present study, we found that GA suppressed the in vitro cell viability and metastasis and inhibited the in vivo tumor growth of HCC cells. The underlying mechanism was further to investigated and it was showed that GA suppressed the expression of β-catenin and led to the functional inactivation of Wnt/β-catenin signaling. As a kind of significant regulators, the long noncoding RNA molecules (lncRNAs) have attracted widespread attentions for their critical roles in diverse biological process and important implications in variety of human diseases. To further identify which lncRNA participated this GA-mediated process, several lncRNAs related to Wnt/β-catenin signaling were chosen for examination of their expression profiling in the GA-treated HCC cells. Of which, Metastasis-Associated Lung Adenocarcinoma Transcript 1 (MALAT1) was the most promising candidate. And MALAT1 was significantly down-regulated by GA. Its overexpression partially reversed the GA-induced the inhibitory cell proliferation and metastasis; and successfully abolished the suppressive effect of GA on Wnt/β-catenin signaling. In conclusion, our results indicated that GA suppressed tumorigenesis and metastasis in vitro and in vivo by the MALAT1-Wnt/β-catenin signaling axis, suggesting that GA has great potential to be developed as a chemo-prevention and chemotherapy agent for HCC patients.